2007
DOI: 10.1518/001872007x230190
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular Response to Cyclic Lumbar Twisting

Abstract: The results of this study increase understanding of the risk factors associated with low back disorder induced by labor-intensive occupations that involve cyclic lateral twisting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…The purpose of these experiments was to confirm that results and conclusions derived from the feline model may be applicable to humans loading their spine under similar conditions. The experimental details are also provided in the individual reports (Solomonow et al, 2003a;Olson et al, 2004Olson et al, , 2006Olson et al, , 2009Li et al, 2007).…”
Section: Human Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of these experiments was to confirm that results and conclusions derived from the feline model may be applicable to humans loading their spine under similar conditions. The experimental details are also provided in the individual reports (Solomonow et al, 2003a;Olson et al, 2004Olson et al, , 2006Olson et al, , 2009Li et al, 2007).…”
Section: Human Experimentsmentioning
confidence: 99%
“…The objective of this paper is to provide a systematic integration of the various components active in the hypothesis (creep, neuromuscular control, stability, inflammation/ tissue biology) obtained from a long series of experimental research projects in animal models (Williams et al, 2000;Eversull et al, 2001;Solomonow et al, 2003bSolomonow et al, , 2008Solomonow et al, , 2011Claude et al, 2003;Hoops et al, 2007;Le et al, 2007;Lu et al, 2004Lu et al, , 2008Navar et al, 2006;Youssef et al, 2008;Le et al, 2009;Ben-Masaud et al, 2009;King et al, 2009;D'Ambrosia et al, 2010;Pinski et al, 2010) and healthy humans (Solomonow et al, 2003a;Olson et al, 2004Olson et al, , 2006Olson et al, , 2009Li et al, 2007) in order to provide a comprehensive model of the multi-factorial etiology of RLI, offer validating support for the acute phase of the hypothesis and allow the potential developments of science based methods for its treatment and prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Olson et al (2004Olson et al ( , 2006, Li et al (2007), Shin and Mirka (2007), Granata et al (2005), Dickey et al (2003) found that such significant changes in muscular activity occur after moderate and mild cyclic loading in humans. In essence, these complementary findings validate that the observations made in this project, using an in vivo cat model, are also seen in humans subjected to similar loading conditions, and that mild loading dose duration can trigger such muscular responses.…”
Section: Article In Pressmentioning
confidence: 84%
“…The epidemiology was recently confirmed biomechanically and physiologically in in vivo models (Navar et al, 2006;Le et al, 2007;Hoops et al, 2007) and in humans (Granata et al, 2005(Granata et al, , 1999Olson et al, 2004Olson et al, , 2006Shin and Mirka, 2007;Li et al, 2007;Dickey et al, 2003;Karajcarski and Wells, 2006). Prolonged periods of exposure to cyclic lumbar loading were shown to develop substantial laxity/ creep in the viscoelastic tissues and in turn, significant changes in the activation pattern of the spinal musculature.…”
Section: Introductionmentioning
confidence: 80%
“…[3][4][5] Cyclic stretch plays role in the growth, maintenance, remodeling and disease onset in the viscoelastic tissues of the spine. 6 As a risk factor for low back disorder, cyclic stretch causes the hypertrophy of LF, leading to degenerative spinal canal stenosis. LF is continuously subjected to a variety of stretch, and the mechanism by which LF cells respond to mechanical forces is not completely understood.…”
Section: Introductionmentioning
confidence: 99%